PERANAN GOOD CORPORATE GOVERNANCE DALAM MEMODERASI PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Sawitri Kemala Putri; St. Dwiarso Utomo (Dinamika Akuntansi Keuangan dan Perbankan, 2021)
Based on the data obtained, this study was made with intention of analyzing the role of good corporate govenance inmoderating profitability and company size against firm value in manufacturing companies listed on the IDX with 3years of observation, namely the 2017-2019 period. The independent variable is proxied using Return On Assets (ROA)as the profitability variable and SIZE as the firm size variable. The moderating variable is proxied using ManagerialOwnership (KM), while the dependent variable uses the proxy Tobins'Q. The population is manufacturing companies in2017-2019 listed on the IDX. The sample taken is 79 manufacturing companies with purposive sampling method. Themethod of analysis uses multiple linear regression. The results of the research tested show that ROA and SIZE have aninfluence on firm value. However, KM is not able to moderate the effect of ROA on firm value. And KM moderates theinfluence of SIZE on firm value.